Timing-Dependent Effects of Fluoxetine and 808 nm Photobiomodulation in CORT/H₂O₂-Stressed SH-SY5Y Cells - Qusay Muslim, Zahraa; Salman, Salman Mohammad; Madhlom, Kaiser N. (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Major depressive disorder is associated with glucocorticoid dysregulation, oxidative stress, inflammation, and mitochondrial disturbance. Cellular systems can examine selected components of these processes but do not reproduce the clinical disorder. To examine the timing-dependent effects of fluoxetine and 808 nm photobiomodulation (PBM), alone and together, in CORT/H₂O₂-stressed SH-SY5Y cells. Methods: SH-SY5Y cells were exposed concurrently to corticosterone and hydrogen peroxide (100 µM each) for 24 h. Fluoxetine (1 µM) and PBM (808 nm, 50 mW, 0.2 cm² beam area, 250 mW/cm², 40 s; calculated nominal fluence 10 J/cm²) were applied before, during, or after stress. Cell viability, malondialdehyde (MDA), reduced glutathione (GSH), and interleukin-6 (IL-6) were assessed. Reported p-values derive from exploratory one-way analyses and do not estimate factorial interactions. Results: The combined stress condition was associated with lower viability and GSH and higher MDA and IL-6 than the control. In the original exploratory comparisons, co- and post-treatment generally showed more favorable viability and redox outcomes than pretreatment. The combined intervention showed favorable mean responses at several time points, with concurrent treatment showing the broadest redox pattern and post-treatment showing the lowest mean IL-6. Conclusion: Fluoxetine and PBM were associated with timing-dependent cytoprotective patterns in this cellular stress system. Because factorial interactions were not tested, biochemical endpoints were not documented as cell- or protein-normalized, and the model does not represent major depressive disorder, the findings are hypothesis-generating and do not establish synergy, mechanism, clinical efficacy, or safety.